“Elaboración de un suplemento proteico en polvo a partir de suero lácteo” . - Sánchez Tapia, Doménica Karolina (2024)
This research was made with the purpose of taking whey advantage got from cheese production in our country, which for many years, was considered waste and generates a negative environmental impact on our environment. Currently, the industry has focused on giving a new opportunity to this byproduct. This work seeks to develop a whey powdered protein supplement from whey concentrate to complement the people's nutritional and protein needs, and further, it contributes to more sustainable practices within the food industry. For elaborating the concentrate, it was used the ultrafiltration and drying technique in a spray dryer, and to elaborate the protein supplement, it was added maltodextrin, organic cocoa powder and a stabilizers mix, to give added value to the product. This research work included a tests series, which resulted in a protein content 30.18% in the best treatment, the microbiological tests made on this treatment comply with the requirement from INEN 2983 standard for nutritional supplements, while the got results, through sensory analysis highlight the treatment 1 acceptability, which contains a 29.48% protein. All the treatments analyzed in this research provide more than 20% the daily protein requirement, being considered a high protein product, according to the INEN 1334:3 standard and has exceptional nutritional properties and attractive sensory characteristics.